3D bioprinting of osteon-mimetic scaffolds with hierarchical microchannels for vascularized bone tissue regeneration. (1st July 2022) - Sun, Xin; Jiao, Xin; Yang, Xue; Ma, Jie; Wang, Tianchang; Jin, Wenjie; Li, Wentao; Yang, Han; Mao, Yuanqing; Gan, Yaokai; Zhou, Xiaojun; Li, Tao; et al.
Abstract: The integration of three-dimensional (3D) bioprinted scaffold's structure and function for critical-size bone defect repair is of immense significance. Inspired by the basic component of innate cortical bone tissue—osteons, many studies focus on biomimetic strategy. However, the complexity of hierarchical microchannels in the osteon, the requirement of mechanical strength of bone, and the biological function of angiogenesis and osteogenesis remain challenges in the fabrication of osteon-mimetic scaffolds. Therefore, we successfully built mimetic scaffolds with vertically central medullary canals, peripheral Haversian canals, and transverse Volkmann canals structures simultaneously by 3D bioprinting technology using polycaprolactone and bioink loading with bone marrow mesenchymal stem cells and bone morphogenetic protein-4. Subsequently, endothelial progenitor cells were seeded into the canals to enhance angiogenesis. The porosity and compressive properties of bioprinted scaffolds could be well controlled by altering the structure and canal numbers of the scaffolds. The osteon-mimetic scaffolds showed satisfactory biocompatibility and promotion of angiogenesis and osteogenesis in vitro and prompted the new blood vessels and new bone formation in vivo . In summary, this study proposes a biomimetic strategy for fabricating structured and functionalized 3D bioprinted scaffolds for vascularized bone tissue regeneration.